2019
DOI: 10.1002/ece3.5366
|View full text |Cite
|
Sign up to set email alerts
|

Are Drosophila preferences for yeasts stable or contextual?

Abstract: Whether there are general mechanisms, driving interspecific chemical communication is uncertain. Saccharomycetaceae yeast and Drosophila fruit flies, both extensively studied research models, share the same fruit habitat, and it has been suggested their interaction comprises a facultative mutualism that is instigated and maintained by yeast volatiles. Using choice tests, experimental evolution, and volatile analyses, we investigate the maintenance of this relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 64 publications
2
22
2
Order By: Relevance
“…Clearly, growth medium can have a marked effect on the attractiveness of fermenting preparations of yeasts [17]. Appropriate mixtures of nutrients at suitable concentrations are critical for high biomass and the production of volatile compounds in yeasts [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clearly, growth medium can have a marked effect on the attractiveness of fermenting preparations of yeasts [17]. Appropriate mixtures of nutrients at suitable concentrations are critical for high biomass and the production of volatile compounds in yeasts [33].…”
Section: Discussionmentioning
confidence: 99%
“…A clear association has been established between some yeasts of the family Saccharomycetaceae and drosophilids because (i) yeasts constitute a key nutritional source that improves fitness, sexual maturation, egg production, and courtship performance of adult flies and (ii) dispersal of yeasts by adult flies increases the dissemination and genetic diversity of these microbes [8,9,10,11,12,13]. Indeed, many species of Drosophila are attracted to volatile compounds produced by fermenting yeasts, or bacterial metabolites of these compounds [14,15,16,17], a feature that could be exploited for the development of effective and selective attractants for use in crop settings. Of the yeast species associated with Drosophila, the majority belong to the genera Saccharomyces, Hanseniaspora , Candida, and Pichia , all within the family Saccharomycetaceae [9,12,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, species-specific attractions have been observed. While D. melanogaster is attracted by S. cerevisiae, D. simulans is indifferent to this yeast species (Gunther et al, 2019). At the same time, D. melanogaster and the subgenus Sophophora are preferentially attracted to baits seeded with Hanseniaspora uvarum than to S. cerevisiae and forest-dwelling Drosophila species (e.g., D. tripunctata and the guarani group) are more attracted by S. cerevisiae than by H. uvarum (Batista et al, 2017).…”
Section: Saccharomyces Cerevisiae-insects Association: the Insect Sidmentioning
confidence: 97%
“…Lewis and Hamby 12 showed that while D. suzukii larvae exhibited a preference for H. uvarum over S. cerevisiae yeast, this preference did not translate to more rapid development time 12 . Given the apparent role of yeast in Drosophila fitness it is reasonable to suggest that natural selection will have operated on Drosophila traits that increase the probability of locating yeast laden-fruits 14 , 15 . In line with this prediction Drosophila females prefer to oviposit on yeast-colonised fruit 13 , and yeast metabolic volatiles act as cues for Drosophila to locate fruit with yeasts (e.g.…”
Section: Introductionmentioning
confidence: 99%